Developing Integrated Marketing Communications Plan for Kirozi Vietnam Brand at 3Fast Co., Ltd. - Nguyen, Tuong Vy (Vietnam-Korea University of Information and Communication Technology, 2025)
Bachelor thesis of Business Administration - Digital Marketing; 2021-2025.